Profil Kepribadian Hardiness Guru Bimbingan dan Konseling di Kota Bandung - Alyaa Nuurul Shoobihah; Euis Farida; Eka Sakti Yudha (Universitas Mathla'ul Anwar Banten, 2021)
PROFILE OF HARDINESS PERSONALITY OF GUIDANCE AND COUNSELING TEACHERS IN BANDUNG CITY. The aims of this study were to determine personality hardiness of guidance and counseling teachers (school counselors) in Bandung City. Paricipants were two people of guidance and counseling teachers in Bandung City. The method used in this research is descriptive qualitative manifold generate descriptive data to describe the behavior of the subject under study. Then the presence of investigators in this study serves as primary research tool. Data collection techniques in this study using the method of interviews. Data analyzed in this study using qualitative data analysis. Validity test in this study using data triangulation technique. The results showed that guidance and counseling teacher has a personality of hardiness that is characterized by its commitment to still be guidance and counseling teacher in the times and increasingly complex problems that exist, can control unexpected situations, and responding to any incident in his work is not considered as threat.